Coping Mechanisms Used by Farmers to Encounter Psychosocial Problems: Literature Review - Enggal Hadi Kurniyawan; Puja Sheylla Riskita Cahyani; Ariska Anisa’ul Khoiriyah; Faisal Kevin Asti Purnomo; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD Production, 2023)
Psychosocial problems in farmers are big problems that are often experienced by farmers and can have a significant impact on their overall welfare. Psychosocial problems that are often found in farmers are climate change, industrial restructuring, crop failure, and even family responsibilities. This study aims to analyze the description of the coping mechanisms used by farmers in dealing with psychosocial problems. The method used in this study was a literature review article from article search engines such as PubMed, Google Scholar, and Science Direct which was analyzed using the PRISMA technique by including articles published in the last 5 years. The results of the study found that the impact of psychosocial problems experienced by farmers includes stress, worry and fear at work, can cause burnout, even threats of suicide because of the demands of the head of the family. Therefore it is necessary to have an appropriate coping mechanism in solving psychosocial problems experienced by farmers. The forms of coping strategies applied are problem focused coping strategies and emotion focused coping strategies.